2013
DOI: 10.2337/db12-1432
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ Impaired Vessel Formation and Angiogenic Factor Expression in Diabetic Ischemic Limbs

Abstract: Decreased collateral vessel formation in diabetic peripheral limbs is characterized by abnormalities of the angiogenic response to ischemia. Hyperglycemia is known to activate protein kinase C (PKC), affecting the expression and activity of growth factors such as vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF). The current study investigates the role of PKCδ in diabetes-induced poor collateral vessel formation and inhibition of angiogenic factors expression and actions. Isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…Excessive angiogenesis exists in diabetic retinopathy and impaired angiogenesis in coronary and peripheral circulations. 1,10,19,26 In our study, there was more frequent collateral formation in the diabetes group. Greater extent of collaterals (more than one-third of the MCA distribution) was also detected in patients with T2DM.…”
Section: Surgical Treatmentmentioning
confidence: 64%
See 1 more Smart Citation
“…Excessive angiogenesis exists in diabetic retinopathy and impaired angiogenesis in coronary and peripheral circulations. 1,10,19,26 In our study, there was more frequent collateral formation in the diabetes group. Greater extent of collaterals (more than one-third of the MCA distribution) was also detected in patients with T2DM.…”
Section: Surgical Treatmentmentioning
confidence: 64%
“…4,8,13 Different outcomes of neovascularization attributed to DM have been found in various organ systems. 1,10,19,26 The effect of DM on cerebral neovascularization remains unclear. In this study, we sought to investigate the effect of EDAS on clinical outcomes and explore the distinction of collateral circulation between MMD patients with and without type 2 diabetes mellitus (T2DM).…”
mentioning
confidence: 99%
“…As a consequence, PKCδ-deficient diabetic mice show significantly increased blood flow, capillary density, and number of capillaries. 30 Finally, angiopoietins and their receptor Tie-2 have been shown to harmonize vascular regeneration in diabetic tissue. Tie-2 expression is significantly reduced, whereas angiopoietin 2 (Ang-2) is increased in Leprdb/Leprdb mice subjected to MI.…”
Section: Additional Angiogenic-related Pathwaysmentioning
confidence: 99%
“…PRKCD is the only protein among the 5 candidate targets of PQS that is known to block angiogenesis [24]. Western blot analysis showed increased expression of PRKCD in ischemic myocardium (vs. sham surgery ; Fig.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…PRKCD, known as PKCδ in porcine species, belongs to the PKC family and is expressed in endothelial cells (ECs) and smooth muscle cells (SMCs) [32,33]. A study in rats demonstrated that PKCδ could impair vessel formation in diabetic ischemic limbs [24], suggesting that PKCδ is a negative regulator of angiogenesis. In our study, we showed PQS could reverse CMI-induced elevation in PRKCD expression, indicating that PQS may promote angiogenesis through blocking the expression of PRKCD.…”
mentioning
confidence: 99%